PENGARUH RATA-RATA LAMA SEKOLAH DAN PERTUMBUHAN EKONOMI SERTA PENYERAPAN TENAGA KERJA TERHADAP PERSENTASE PENDUDUK MISKIN - Muhamad Arif W.; Siti Umajah i Masjkur (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2018)
Introduction: East Java is one of the provinces with good economic performance: high economic growth accompanied by increased employment, increased average length of schooling, and decreased poverty. However, the poverty rate in East Java is still relatively high. This study aims to examine and analyze the effect of the average length of schooling, economic growth, and labor absorption on the percentage of poor people in districts and cities in East Java in 2007-2011. Methods: This study uses the path analysis method. This method was chosen because it is able to explain the direct and indirect effects between the independent variables and between the independent variables and the dependent variable based on a model built from previous theory and research. Results: The results showed that the average length of schooling had a negative effect on labor absorption, labor absorption had a positive effect on the percentage of poor people, so that the average length of schooling had an indirect negative effect on the percentage of poor people through labor absorption. Economic growth has a direct positive effect on labor absorption and indirectly on the percentage of poor people, but has a direct negative effect on the percentage of poor people. Conclusion and suggestion: It is necessary to map the quality and specifications of education required by employment. The link and match program between the world of work and education needs to be reconsidered, not only in higher education but also at secondary level education.